Photo elastic analysis of stresses in the root canal walls around double taper and - Zafar Mahdavi Ezadi; Ezatolah Jalalian; Mohamad Hasan Salari; Shima Azimzad; Tahmine Safaie; Mahdi Shirazi; Behzad Salari (Tehran University of Medical Sciences, 2013)
Background and Aims : According to the common application of non-metal prefabricated posts in dentistry and lack of enough information about the stress distribution in the root canal walls by these posts, this study was performed to compare the effect of two simple taper and double taper posts on the stress distribution on root canal walls by photo elastic method .   Materials and Methods: The design of this study was experimental in photoelastic system. The posts, used in this investigation, were double taper and simple taper fiber posts with 0.9 mm diameter and 20 mm length and epoxy resin. First two photo elastic models with tooth dimensions were fabricated and the posts were placed inside the model. Then the core of the each post was fabricated on the model. Each models were loaded in polariscope and the formed fringe order colored ring were photographed.   Results: In 100 N, 90 degree angle loading in cervical and apical fringe order showed 2.50 and 1.39 in simple taper posts and 1.39 and 2.35 in double taper post. In 150 N, 30 degree angle loading in cervical and apical fringe order showed 4 and 2.65 in simple taper posts, and 4 and 2.5 in double taper post.   Conclusion: In the vertical and oblique loads, double taper fiber post showed better stress distribution than that of simple tapered posts.